2013
DOI: 10.1016/j.aeolia.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of spatial variability in aeolian dune and interdune morphology in the Rub’ Al-Khali, Saudi Arabia

Abstract: The Rub' Al-Khali aeolian sand sea of south eastern Saudi Arabia -also known as the Empty Quarter -covers an area of 660,000 km² and is one of the largest sandy deserts in the world. The region is covered by the latest generation of public-release satellite imagery, which reveal spatially diverse dune patterns characterized by a varied range of dune types, the morphology, scale and orientation of which change systematically from central to marginal dune-field areas where non-aeolian subenvironments become domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…Significant diversity in the arrangement and type of interaction of competing depositional sedimentary systems is recognised in modern desert dune fields and their marginal areas, and these give rise to complex yet predictable geomorphological patterns that commonly vary over space and time (e.g. Lancaster, 1989;Cooke et al, 1993;Bullard and Livingstone, 2002;Al-Masrahy and Mountney, 2013). The record of these interactions is also recognised in the ancient sedimentary record (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Significant diversity in the arrangement and type of interaction of competing depositional sedimentary systems is recognised in modern desert dune fields and their marginal areas, and these give rise to complex yet predictable geomorphological patterns that commonly vary over space and time (e.g. Lancaster, 1989;Cooke et al, 1993;Bullard and Livingstone, 2002;Al-Masrahy and Mountney, 2013). The record of these interactions is also recognised in the ancient sedimentary record (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The mechanism controlling superimposition is debated with large‐scale changes in wind regime and climate (Warren and Allison, ), seasonal or annual variation in wind (Bristow et al, ), landscape patterning and self‐organisation (Ewing et al, ; Dong et al, ) and stabilisation of the underlying dune due to climatic change (Dong et al, ) all suggested as potential drivers. There is some evidence that the size of the dune determines the quantity and complexity of superimposed features with secondary features unable to form where the primary dune is below a certain size (Breed and Grow, ; Al‐Masrahy and Mountney, ). Thus, secondary dunes may simply be a function of airflow fluctuation created when the flanks of the dunes are large enough to form a planar surface (Lancaster, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Wood et al. ; Al‐Masrahy and Mountney ). Long‐term climatic data for the study were obtained from the Environment Canada – Fort Chipewyan (58°46” N; 111°07’“W) weather station located approximately 115 km south‐east of Athabasca dune fields, as this was the closest station with long‐term weather data available (Carson and MacLean ).…”
Section: Methodsmentioning
confidence: 99%